Ekuitas Merek Platform Berbasis Teknologi di Instagram - Raden Muhammad Jihad Muharram; Anne Ratnasari (UNISBA Press, 2023)
Abstract. The title of this research is “TECHNOLOGY BASED PLATFORM BRAND EQUITY ON INSTAGRAM (Case Study on Instagram @readylearn social media)” The rapid development of the times is increasingly refining technology on the Internet. Especially in education, where technology-based platforms are already in use, technology can complete a variety of disciplines. Various kinds of platform brands have been born in the field of education to help the knowledge of Indonesian people. Therefore, researchers are interested in conducting a survey on ReadyLearn through a survey called